Storage of Imidaclopride and Acetamyprid in Biological Objects and Study of Conservative Effects on This Process - Yuldashev, Zakirdjan Abidovich; Nurmatova, Malokhat Ismatovna (RA Journal of Applied Research, 2021)
In this article is studied the biological conditions of imidacloprid and acetamiprid pesticides under laboratory conditions and the storage of the objects in a state preserved in ethyl alcohol. There were determined in the composition of the biological object stored in the laboratory the imidacloprid was detected after 13.07% in 90 days and in objects preserved with ethyl alcohol - 14.05%. When the biological object containing acetamiprid was analyzed after 90 days, it was found to be 4.45%, and when the object was stored under 95% ethyl alcohol5.72%. In the analysis of acute poisoning cases with imidacloprid and acetamiprid, it is recommended that their shelf life should be taken into consideration.